ANALISIS PENINGKATAN KAPABILITAS APARAT PENGAWASAN INTERN PEMERINTAH MENGGUNAKAN INTERNAL AUDIT-CAPABILITY MODEL (Studi Kasus pada Inspektorat Kabupaten Sidoarjo) - ANGGIE PRAMAI SELLA (Jurnal Ilmiah Mahasiswa FEB, 2019)
This research aims to identify the capabilities of Government Internal Supervisory Apparatus in the inspectorate ofSidoarjo regency, to identify obstacles faced by the inspectorate in improving its supervisory management, and todetermine efforts to improve the capability of the apparatus. This qualitative case study uses primary data fromobservation, documentation, and interviews and secondary data. This study finds that the capability of theinspectorate of Sidoarjo regency is on level 3 with notes. The inspectorate is still struggling with poor infrastructure,auditor’s consistency, auditor's and regional head’s commitment, human resource, and budget. Therefore, theinspectorate should build more facilities, increase human resource’s competence, establish tiered review controls,provide rewards (package systems), reduce independency, hire more auditors, and increase its budget.Keywords: Capability, Government Internal Supervisory Apparatus, Inspectorate, Internal Audit Capability Model